The Role of Islamic Ethics in Leading the Man to Perfection - Ismail Kharestani; Fatemeh Seyfi; Kazem Manafi Sharafabad (اخلاق وحیانی)
The purpose of the present research is to study the role of Islamic ethics in leading the man beings to perfection. The research method adopted is of document analysis and descriptive kind. The research domain included the primary sources (including the holy Quran, and the resources attributed to the Prophet of Islam and the pure Imams as well as the works of great religious scholars) and secondary sources (scientific works derived from rich Islamic resources) which include books, journals, dissertations, religious internet websites and other research studies related to this study. Sampling was done through purposive sampling, thus only the resources related to the topic of this research were utilized. Moreover, the instrument of research has been note-taking in this study. This study aims at answering the following questions: What is the role and significance of ethics in the viewpoint of Islam? What is the role of ethics in the personal and social life from the perspective of the Quran and that of the infallibles? What are the incentives of individuals in striving for perfection? What are the ethical principles and practices for leading mankind to perfection from the viewpoint of the Quran and the infallibles? The results of this study indicated that the ethical practices explicated by the Quran, the Prophet of Islam, and the pure Imams have indeed illuminated the way to perfection for mankind, by practicing which, true perfection can be achieved. Finally some implications and suggestions have been presented to make the results of this research practical.